Determinants of ethical financial behaviour and well-being among Malaysian tertiary students - Lee, Eunkyoung; Rahim, Hainnuraqma; Hasbullah, Nornajihah; Zakaria, NorBalkish; Bakar, Mohd Hafiz (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
Financial problems and stress among Malaysian tertiary students could be instigated by poor financial management. This study assessed Malaysian tertiary students’ financial literacy, money ethic, financial knowledge and family influence in explaining Financial Well-Being (FWB) through ethical f inancial behavior. Ethical financial behavior it was introduced as a mediator via online survey questionnaires and 134 of the 200 questionnaires that were delivered were used for analysis. Employing Partial Least Squares Structural Equation Modelling (PLS-SEM), this study evaluated the hypotheses. The findings indicated that ethical financial behavior acted as the primary precursor, succeeded by money ethics and familial influence in forecasting FWB. Thus, achieving FWB among Malaysian tertiary students necessitatesa balance between money ethic and expenditure, alongside the management of financial literacy and knowledge. It is imperative for governmental and financial institutions to amplify their roles and initiatives towards cultivating a financially literate and adept society. This research provides complementary insights into financial comprehension, aiding the development of ideas associated with financial management, which prove advantageous not only for students but also for society at large.